(untitled) (Conferencea, 2023)
In recent years, increasing numbers of professional development programs have dealt with assessment literacy for teachers. Assessment literacy is seen, therefore, as a sine qua non for today’s competent educator. As such, assessment literacy must be a pivotal content area for current and future staff development endeavors. Assessment literacy has been increasingly touted as a fitting focus for teachers’ professional development programs. This article deals with assessment literacy that is typically recommended refers to a teacher’s familiarity with those measurement basics related directly to what goes on in classrooms. Given today’s ubiquitous, externally imposed scrutiny of schools, we can readily understand why assessment literacy might be regarded as a likely target for teachers’ professional development. Yet, is assessment literacy a legitimate focus for teachers’ professional development programs.